2005
DOI: 10.1515/znc-2005-9-1018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Genetic Diversity of the Liver Fluke Fasciola hepatica

Abstract: Economical breeding is important to obtain maximum gain from the breeding in the animal sector. The economic loss has to be eliminated or should be minimized. The liver fluke, Fasciola hepatica, present mostly in sheep and dairy cattle affect the yield of animals and even cause their death. To eliminate or minimize the impact of these parasites on the animals, it is important to understand the genetic diversity of the liver fluke populations and the relationship between parasite and host at regional bases. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This is comparable to the 1 to 7% reported elsewhere (Dosay-Akbulut et al 2005) for both the ribosomal ITS 1 and mitochondrial ND1 genes of the fluke. These values are approximately twice greater than those reported by Blouin et al (1999) working with the parasitic nematode Heterorhabitis marelatus, using values derived from an analysis of a 600-bp fragment contained within the approximately 7,000-bp sequence used in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is comparable to the 1 to 7% reported elsewhere (Dosay-Akbulut et al 2005) for both the ribosomal ITS 1 and mitochondrial ND1 genes of the fluke. These values are approximately twice greater than those reported by Blouin et al (1999) working with the parasitic nematode Heterorhabitis marelatus, using values derived from an analysis of a 600-bp fragment contained within the approximately 7,000-bp sequence used in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The recent development of microsatellite markers (Hurtrez-Bousses et al 2004) and their application to Bolivian samples of F. hepatica from cattle, sheep, and pig hosts have similarly indicated the existence of genetic polymorphism between flukes from distinct definitive hosts, but again, little detail of the source of these flukes was given. Dosay-Akbulut et al (2005) used the DNA sequencing of part of the mitochondrial ND1 gene to show that, although flukes from sheep and cattle were not distinct, evolutionary lineage differences between individual flukes may be detected using mitochondrial DNA. However, this study was again limited in the number of samples analysed and lacked detail with regards to their provenance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have characterized Fasciola from different countries using genetic approaches (Itagaki and Tsutsumi 1998;Agatsuma et al 2000;Huang et al 2004;Alasaad et al 2007;Lin et al 2007;Vara-Del Río et al 2007;Alasaad et al 2008;Ali et al 2008;Le et al 2008;Lotfy et al 2008); however, little is known about genetic identification of F. hepatica from Turkey (Dosay-Akbulut et al 2005;Kuk et al 2005Kuk et al , 2006Semyenova et al 2006). Therefore, the objective of the present study was to describe the molecular identification of the F. hepatica samples from different geographical locations in Turkey (Elazig, Malatya, Samsun) by sequences of the ITS-2 rDNA.…”
Section: Introductionmentioning
confidence: 95%
“…The other also came from eastern Europe and central Asia. A more limited study, developed in Turkey, showed the diversity of F. hepatica strains by sequencing the mitochondrial gene nad1 and the ribosomal part ITS1 (Dosay-Akbulut et al, 2005). Other previous studies (Marcilla et al, 2002;Ramadan & Saber, 2004) were developed to distinguish F. hepatica from F. gigantica, particularly in countries where both species are sympatric.…”
Section: Diversity Of Parasites In the Paragonimus Genusmentioning
confidence: 99%